Formulation and Evaluation of Helichrysum italicum Essential Oil-Based Topical Formulations for Wound Healing in Diabetic Rats - Marijana Andjić; Biljana Božin; Nevena Draginić; Aleksandar Kočović; Jovana N. Jeremić; Marina Tomović; Andjela Milojević Šamanović; Nebojša Kladar; Ivan Čapo; Vladimir Jakovljević; Jovana V. Bradić (MDPI AG, 2021)
As proper wound management is crucial to reducing morbidity and improving quality of life, this study evaluated for the first time the wound healing potential of H. italicum essential oil (HIEO) prepared in the form of ointment and gel in streptozotocin-induced diabetic wound models in rats. After creating full-thickness cutaneous wounds, forty-eight diabetic rats were divided into six groups: (1) negative control; (2) positive control; (3) ointment base; (4) gel base; (5) 0.5% HIEO ointment (6) 0.5% HIEO gel. Wound healing potential was determined by the percentage of wound contraction, hydroxyproline content, redox status, and histological observation. A significant decrease in the wound size was observed in animals treated with HIEO formulations compared with other groups. The HIEO groups also showed a higher level of total hydroxyproline content, and more pronounced restitution of adnexal structures with only the underlying muscle defect indicating the incision site. Hence, our results legitimate the traditional data of the pro-healing effect of HIEO because HIEO in both formulations such as gel and ointment exhibited the significant wound repairing effect in the incision wound model.